Clinico-epidemiological features and outcome of dengue cases admitted in a tertiary care centre in Northern Kerala - Thomas, Renu; Anees, Shamseeda; Kumaran, Jayasree Anandbhavan (International Journal Of Community Medicine And Public Health, 2021)
Background: Dengue is now emerging as a public health problem of global concern. Though dengue is endemic in Kerala, occasional outbreaks of dengue has been reported from the state. It is therefore essential to study the epidemiological factors playing a role in the transmission of the disease, which is crucial to limit the surge in dengue cases. By describing the clinical profile and outcome, better patient management can be practiced thereby reducing complications and mortality. Methods: A record based descriptive study done in a tertiary care centre in North Kerala. A total of 327 clinically diagnosed dengue cases admitted in the tertiary care centre during June and July months were included in this study. Results: Out of the total 327 dengue cases included in the study, 101 (31%) had dengue fever, 220 (67%) had DHF and 6 (2%) had DSS. Majority 41.9% were in the age group 40-59 years of age. Majority 88.1% were from rural area. Rubber plantation (40.9%) was identified as the most common source of artificial collection of water.78.9% reported having similar dengue cases in the locality. Fever (87.1%), headache (55.3%), body ache (50.4%) were the common clinical presentation. 94.5% of cases with DHF were cured within 7 days. 33.3% of DSS cases required hospital admission for more than 7 days. Conclusions: The present study inferred that, breeding premises, within the same household and in the same locality are some of the factors playing a role in transmission of dengue. With the ongoing COVID-19 pandemic, active public health surveillance of dengue has to be enforced. Appropriate referral to higher centres reduce complications and mortality.